THE UNIQUENESS OF TELEK DANCE IN JUMPAI VILLAGE - Ni Luh Putu Mirah Pratiwi; Putu Agus Permanamiarta (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Telek dance inJumpai village is a guardian or sacred dance. The dance is still maintained from generation to generation, preserved and maintained. this dance is a heritage dance that must be performed by the residents of the village because local residents believe that the dance is a form of repellent to reinforcements in order to be given safety and keep Jumpai village away from the plague, the dance is performed once every 15 days which coincides with rahinan kajeng kliwon. The Telek dance in Jumpai village is estimated to have developed around 1935 until now. the Telek dance in there was performed by 4 male and female dancers who were still classified as children (approximately 6-12 years old). The purpose of this research is to show the value of function and meaning in Telek dance in Jumpai village. The values in Telek dance include; religious values, cultural values, knowledge values, and skills values. This dance is danced with a duration of 14 minutes.